Synthesis of Oligobenzamide α-Helix Mimetics - Burslem, George M.; Wilson, Andrew J. (Synlett, 2014)
The development of inhibitors of protein–protein interactions (PPIs) represents a major challenge in chemical biology. α-Helix-mediated PPIs represent a subclass that might be amenable to inhibition using scaffolds that reproduce the spatial projection of recognition groups produced by the helix; these ligands are termed proteomimetics. Such a generic scaffold approach requires robust chemistry that can be used to synthesize reasonably large libraries of compounds. Foldamers are defined as oligomers that adopt well-defined folded structures. An ultimate goal of research in this area is to be able to reproduce and surpass the functionality of natural biopolymers; again a key enabling technology in this pursuit is robust synthetic methodology with a broad substrate scope. When we started our research program in this area seven years ago, we were drawn to aromatic oligoamide foldamers as potential proteomimetic scaffolds; however, in contrast to more widely studied β-peptide- and peptoid-based foldamers, the synthesis of aromatic oligoamides was less well developed in terms of monomer diversity and amenability to library synthesis. This account describes our efforts and, more generally, the development of methodologies for the synthesis of aromatic oligoamides during this period.1 Introduction1.1 Helix Mimetics-Based on Aromatic Oligoamides1.2 Issues with Amide Bond Formation2 N-Alkylated Oligobenzamides3 O-Alkylated Oligobenzamides4 Concluding Remarks
Keywords: amides; oligomerization; peptidomimetics; solid-phase synthesis